2008
DOI: 10.1105/tpc.108.059733
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine Exodus and Oxidation in the Apoplast Induced by Abiotic Stress Is Responsible for H2O2 Signatures That Direct Tolerance Responses in Tobacco

Abstract: Polyamines (PAs) exert a protective effect against stress challenges, but their molecular role in this remains speculative. In order to detect the signaling role of apoplastic PA-derived hydrogen peroxide (H 2 O 2 ) under abiotic stress, we developed a series of tobacco (Nicotiana tabacum cv Xanthi) transgenic plants overexpressing or downregulating apoplastic polyamine oxidase (PAO; S-pao and A-pao plants, respectively) or downregulating S-adenosyl-L-methionine decarboxylase (samdc plants). Upon salt stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
262
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 295 publications
(291 citation statements)
references
References 35 publications
21
262
0
8
Order By: Relevance
“…8) similarly to ZmPAO overexpression in the cell wall, suggesting that xylem differentiation and PCD induction are governed by a complex regulatory system in which intracellular PAs and apoplastic PAderived H 2 O 2 are likely integrated in coordinated signaling pathways; this is consistent with a previous hypothesis where salinity-induced cell death was proposed to be governed by the PAs/H 2 O 2 ratio (Moschou et al, 2008b). In this regard, Moschou et al (2008aMoschou et al ( , 2008b reported that the balance between the apoplastic PA catabolism versus the intracellular PA levels plays a central role in plant responses to salinity by governing the cell fate decision, leading to either induction of PCD or to tolerance mechanisms. Specifically, it was proposed that lowering the PA anabolism/PA catabolism ratio promotes PCD (S-ZmPAO and RNAi-SAMDC plants), while if PA anabolism predominates over catabolism, PCD fails to occur, allowing simultaneous induction of stress-responsive genes and plant tolerance (wild-type and A-ZmPAO plants).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…8) similarly to ZmPAO overexpression in the cell wall, suggesting that xylem differentiation and PCD induction are governed by a complex regulatory system in which intracellular PAs and apoplastic PAderived H 2 O 2 are likely integrated in coordinated signaling pathways; this is consistent with a previous hypothesis where salinity-induced cell death was proposed to be governed by the PAs/H 2 O 2 ratio (Moschou et al, 2008b). In this regard, Moschou et al (2008aMoschou et al ( , 2008b reported that the balance between the apoplastic PA catabolism versus the intracellular PA levels plays a central role in plant responses to salinity by governing the cell fate decision, leading to either induction of PCD or to tolerance mechanisms. Specifically, it was proposed that lowering the PA anabolism/PA catabolism ratio promotes PCD (S-ZmPAO and RNAi-SAMDC plants), while if PA anabolism predominates over catabolism, PCD fails to occur, allowing simultaneous induction of stress-responsive genes and plant tolerance (wild-type and A-ZmPAO plants).…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, it was proposed that lowering the PA anabolism/PA catabolism ratio promotes PCD (S-ZmPAO and RNAi-SAMDC plants), while if PA anabolism predominates over catabolism, PCD fails to occur, allowing simultaneous induction of stress-responsive genes and plant tolerance (wild-type and A-ZmPAO plants). Indeed, the RNAi-SAMDC plants, while keeping normal apoplastic Spd exodus and oxidation, exhibited constitutively lower intracellular PA levels as well as enhanced H 2 O 2 production under salt stress in comparison to wildtype plants, with a PAs/H 2 O 2 ratio analogous to that shown by S-ZmPAO plants, which also exhibited lower Spd and Spm levels and higher H 2 O 2 production than the wild-type plants (Moschou et al, 2008b). In agreement with the hypothesis based on the PA/H 2 O 2 ratio, our results showed that lowering the PAs/H 2 O 2 ratio, by either increasing H 2 O 2 production (S-ZmPAO transgenic plants; Fig.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…H 2 O 2 has long been known as a signal molecule. It is able to mediate various processes, such as stomatal closure, directly due to its ability to influence ion channels, while it can also activate specific stress response processes through the MAPK cascade [47]. Polyamines, especially spermidine, also induce superoxide anion (O 2˙-) production by the activation of NADPHoxidase.…”
Section: Signaling Components Providing Linkage Between Polyamines Anmentioning
confidence: 99%